Landscape and business’ risks: History and climate (Rural Russia) - RUDNEV VIACHESLAV (Journal of Advanced Research in Social Sciences and Humanities, 2020)
Aim: This study aimed to ascertain the potential risks associated with a given landscape within the context of the influence of a given climate. Information about the local climate and how the land has been used throughout history is emphasized. In the last few decades, extremely hot weather has become a significant factor in Eurasian society, life, and business. In 2010, an abnormally hot summer in the center of European Russia led to a fire in peat areas and a poor harvest of potatoes and cereals. On July 29th, 2010, a record-breaking heat wave (38.2 degrees Celsius) and massive forest fires ravaged millions of acres in European Russia.Method: A qualitative method was employed to accomplish the goal. Secondary resources were used to compile the data.Findings: The findings demonstrate that current academics expect civilization to usher in two concrete responses to global warming. The two-way street is contemporary culture. There is widespread agreement among agricultural experts that a shift in the seed-planting window or the selection of alternative crops will be necessary if the planet’s average temperature rises. The use of new crop rotation methods could be beneficial.Implications/Novel Contribution: Since it depends on social and cultural conditions, the local ecosystem, and environmental changes, writing a history of human landscape change is challenging. Businesses operating in rural areas usually respond appropriately to all these factors. There has been a lot of focus on this.